Trait priorities for irrigated rice in Southern Asia and South-eastern Asia - Ynion, Jhoanne; Custodio, Marie Claire; Demont, Matty (International Rice Research Institute, 2024)
This article highlights trait priorities for irrigated rice cultivation in Southern and Southeastern Asia, based on insights gathered through CGIAR's Market Intelligence initiative. By integrating data from Investment Game Application (IGA) experiments, the Global Market Intelligence Platform (GloMIP), geospatial information, and breeder consultations, the study identifies key trait priorities for rice varieties in different regions. It explores the challenges of old varieties being preferred by farmers despite the introduction of new ones and emphasizes the importance of understanding farmers’ needs for pest and disease resistance in shaping breeding programs and investment decisions across four major rice-growing areas.